Spray processing and wear characteristics of Al-Cu-Al2O 3-Pb based composites - Anil M.; Ojha S.N. (My University, 2025)
The spray deposition process has been employed in synthesis of Al-4.5Cu-10Al2O3 and Al-4.5Cu-10Al2O 3-10Pb based composites. The microstructure and wear characteristics of composites were investigated. The rapid solidification inherent in spray deposition processing resulted in a uniform dispersion of Al2O 3 and Pb particles co-existing in the matrix of the- primary α-phase. The grain size of the Al-4.5Cu-10Al2O3-Pb composite was observed to be higher than that of the Al-4.5Cu-10Al 2O3 composite in various sections of the spray deposit. The wear rate of composite materials decreased with addition of Pb phase. This behavior is discussed in the light of the microstructural modification induced by spray deposition and the morphology of debris particles on the wear track surfaces. The wear characteristics of the composites are compared with that of the liquid immiscible Al-4.5Cu-10Pb alloy. © 2006 Springer Science + Business Media, Inc.